Manajemen Proyek Berbasis Web - Agung Wijoyo; Muhammad Hafiz BM; Rifaldie Muhammad; Basir; Bayu Aji P.; Supri Wahyudi (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Project management application is an application designed to help and facilitate project management. This project management application is a new breakthrough in terms of project management and as an alternative to desktop-based project management applications because it has the advantage of a real time system or can be monitored remotely at any time. This application focuses on the tasks assigned by the project head to employees or project staff. to be clear in the division of tasks and can be completed on time. The purpose of this research is to build a web-based project management application that focuses on the project management process so that the project is completed as expected. The benefit of developing this application is to help project management so that the project becomes more organized, easier and faster to complete. The tasks to be carried out are clear and directed to the employees.